If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(2x + -1) = 1 Reorder the terms: 5 + -1(-1 + 2x) = 1 5 + (-1 * -1 + 2x * -1) = 1 5 + (1 + -2x) = 1 Combine like terms: 5 + 1 = 6 6 + -2x = 1 Solving 6 + -2x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -2x = 1 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = 1 + -6 -2x = 1 + -6 Combine like terms: 1 + -6 = -5 -2x = -5 Divide each side by '-2'. x = 2.5 Simplifying x = 2.5
| 4(-2-0,5x)=(x+2)(-3) | | 5x-3=6+2x-9 | | 3+n=5n+7 | | 7-0.25s=f-3 | | -3x+6=2x-9 | | 5y+6=-18-y | | 32-2x^4=0 | | 10x+30=21+1x | | 4x+1+3x+2x+2+3+x+4=5(2x+2) | | 3a^2+ab=b^2 | | -9x^2-7+4x+11x^2-13x= | | =4x-5-2x-4 | | 5x^2-12x+10=0 | | 2a^2-17-9=0 | | 3a^2+2ab=b^2 | | (x+6)*(x-5)= | | 8t-15=6t-3 | | (2x-3)(2x-3)=2x | | 22x+5y=3200 | | 10x-3(2x-4)=12 | | 6n^2-18n=6 | | y^2-8y+16= | | x^2-11x+19=-2 | | 0=x^2+5 | | 8k^2-6k-5=0 | | 7x+6y=-9 | | -2x^2+5x+11=0 | | (y-10)(y+10)= | | (y-10)*(y+10)= | | (y-10)X(y+10)= | | (49x*7x+8x*4x)=57 | | 28x^2-51x-27=0 |